2010
DOI: 10.1111/j.1399-6576.2010.02239.x
|View full text |Cite
|
Sign up to set email alerts
|

Definitions of hypotension after spinal anaesthesia for caesarean section: literature search and application to parturients

Abstract: There is not one accepted definition of hypotension in the scientific literature. The incidence of hypotension varies depending on the chosen definition. Even minor changes of the definition cause major differences in the frequency of hypotension. This makes it difficult to compare studies on interventions to treat/prevent hypotension and probably hampers progress in this area of research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
192
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(210 citation statements)
references
References 70 publications
7
192
1
10
Order By: Relevance
“…ephedrine, 10 mg, was given repeatedly [22]. If HR was < 50 beats/ min, 0.6 mg of atropine sulphate was administered intravenously.…”
Section: Discussionmentioning
confidence: 99%
“…ephedrine, 10 mg, was given repeatedly [22]. If HR was < 50 beats/ min, 0.6 mg of atropine sulphate was administered intravenously.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Klohr et al [1] found across 63 publi cations that the incidence of spinal hypotension was 27% when defined as a systolic blood pressure (SBP) <70% of baseline, but that it increased to 39% using an SBP of <75% of baseline. Up to 80% of spinal anaesthetics in obstetrics require the use of a vasopressor to treat hypotension.…”
Section: Incidence and Definitionmentioning
confidence: 99%
“…Autonomic indices such as heart rate variability have also shown promise, [12] but have yet to be translated into a practical clinical tool. Given the high incidence of hypotension, [1,9] research in this area should focus on predicting which patients will have severe hypotension, where outcomes relating to maternal and fetal safety are more likely to be affected. We need simple clinical parameters that identify high risk patients and can be coupled to preventive strategies or earlier referral to specialist centres.…”
Section: Prediction Of Obstetric Spinal Hypotensionmentioning
confidence: 99%
“…Hypotension was defined as SAP less than 80% of baseline -the value accepted by most investigators. (32)(33)(34) In case of hypotension, a bolus of 100 mcg of intravenous phenylephrine was given as a rescue medication with no additional fluid. If there was concomitant bradycardia (heart rate < 50 beats/min), a bolus of 0.5 mg atropine was given.…”
Section: Methodsmentioning
confidence: 99%